2022
DOI: 10.1001/jamasurg.2021.6496
|View full text |Cite
|
Sign up to set email alerts
|

Association of Weight Loss Achieved Through Metabolic Surgery With Risk and Severity of COVID-19 Infection

Abstract: IMPORTANCEObesity is an established risk factor for severe COVID-19 infection. However, it is not known whether losing weight is associated with reduced adverse outcomes of COVID-19 infection.OBJECTIVE To investigate the association between a successful weight loss intervention and improved risk and severity of COVID-19 infection in patients with obesity. DESIGN, SETTING, AND PARTICIPANTSThis cohort study involved adult patients with a body mass index of 35 or higher (calculated as weight in kilograms divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…Among our patients, greater per cent weight loss was associated with lower likelihood of hospitalisation. A recent retrospective, matched cohort study similarly observed that in people with or without type 2 diabetes, prior substantial weight loss (20.8%) resulting from surgery was associated with a 49% lower risk of hospitalisation relative to a control group who lost only 2.3% body weight on average 10. This suggests that clinically significant weight loss achieved through a variety of interventions may improve COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…Among our patients, greater per cent weight loss was associated with lower likelihood of hospitalisation. A recent retrospective, matched cohort study similarly observed that in people with or without type 2 diabetes, prior substantial weight loss (20.8%) resulting from surgery was associated with a 49% lower risk of hospitalisation relative to a control group who lost only 2.3% body weight on average 10. This suggests that clinically significant weight loss achieved through a variety of interventions may improve COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…The relationship between obesity and infectious diseases is not unique to influenza virus. Epidemiological data and studies in obese mice demonstrate obesity is a risk factor for severe COVID-19 26,83 and other infectious diseases 84,85 , and weight loss has been associated with improved outcomes 86 . Additionally, other host-directed interventions may improve vaccine efficacy.…”
Section: Discussion (1313)mentioning
confidence: 99%
“…We also found that the proportion of individuals attaining weight loss of ≥ 5% in the Pre-PC and the PC were not different, which is clinically meaningful to patients with T2D and prediabetes given that weight loss of 5% or more is associated with improvements in glycemic control and cardiovascular risk markers ( 21 , 22 ). Considering the reported benefits associated with weight loss in reducing COVID-19 symptom severity including hospitalization ( 23 25 ), and since our intervention has been reported to improve obesity-related comorbidities like T2D and hypertension as well as markers of systemic inflammation ( 26 , 27 ), future research should evaluate the relationship between weight loss induced by carbohydrate restriction and the severity of illness due to COVID-19 infection ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%